(untitled) (REMUNOM, 2024)
People Management aims to achieve organizational success when aligning effectively human efforts. This study aimed to analyze the application of management processes in People Management within the construction sector. For such, he was qualitative research was carried out, classified in terms of purposes as descriptive and applied, through bibliographic references. Data were collected through scientific articles, magazines and books. The results obtained evidence organizations that provide effective means of identifying and valuing each person’s individual skills. In contemporary Civil Engineering practices, people took on a role central role as the most crucial resource to generate value and achieve organizational objectives. This bounces the importance of exploring this field in Administration, using processes and tools to help managers overcome the obstacles that he has limited historically progress in civil construction. Keyword: People Management; People development; People Training; Civil construction.